Measuring employee performance in Gweru and Kwekwe city councils in midlands province, Zimbabwe - Vonai Chirasha; Crispen Chipunza; Lewis Dzimbiri (Academic Journals (A J), 2023)
For organizations to measure the performance of its employees there is a need to have key performance indicators and performance standards set. The current study at Gweru and Kwekwe City Councils in Zimbabwe assessed eight (8) performance aspects, which are quality work, employee output, communication and dependability (customer), controlling of costs (financial), planning, team working, problem solving and technical understanding (internal methods/organization procedure) and leadership management (learning and growth potential). The study was a quantitative descriptive survey that allowed managers to appraise employee performance. All 32 line managers participated in the research, and 400 employees were selected using stratified random sampling by departments, as employees reported to the same managers. The constructs that measured employee performance were reliable with Cronbach's Alpha reliability coefficients ranging from problem analysis and resolution (0.734), employee controlling costs (0.794), planning and organizing (0.796), employee output (0.778), employee communication (0.823), employee leadership (0.8333) and employee dependability (0.861). Generally, employee performance with regard to quality service for customer needs, financials, internal procedures and learning and growth was low. The technical understanding attribute of performance among employees as determined by managers had the least mean score (12.4%), indicating that public sector organizations like city councils in Zimbabwe, may still engage ‘Rocks' kind of employees. Rocks are the kind of employees who are incompetent because they do not have the technical understanding to do the job and they seem not to care. It is recommended that managers in Gweru and Kwekwe city councils should come up with rigorous training and development policies and practices that help employees acquire relevant skills. Performance indicators should be clearly communicated to all employees. The Gweru and Kwekwe city councils should develop a performance management system that is linked to their performance goals. Constant performance feedback should be given to both managers and employees.